Immunoregulation role of the erythroid cells - Niu, Chunxiao; Zhang, Jiyan (Frontiers in Immunology, 2024)
Erythroid cells are the most abundant cells in the human body. In addition to their established function in gas-transportation, erythroid cells at various stages of differentiation have recently been shown to have immunomodulatory roles. Red blood cells may serve as modulators of innate and adaptive immunity, while their immature counterparts, CD71 + erythroid cells (CECs) have important immunomodulatory functions in various contexts. CECs are abundant in human cord blood and placenta, where they contribute to fetomaternal tolerance. CECs also accumulate in patients with infections, tumors, and anemia, and effectively suppress T cells by producing high levels of arginase, reactive oxygen species, programmed death-ligand 1, transforming growth factor β, and/or interleukin-10. Here, we systematically summarize the immunomodulatory functions of erythroid cells and propose some potential therapeutic applications based on their characteristics.